Minimum wage is efficient wage in Turkish labor market: TAR-cointegration analysis - Bildirici, Melike E.; Alp, Elcin Aykac (SPRINGER, 2012)
This study has two main purposes. First one is the necessity of taking minimum wages into account, if there is a purpose to analyze the relationship between wages and productivity in an economy which has high unemployment rates and informal employment. Second one is about the analyzing method of this relationship. We choose TAR cointegration analysis for this relation. First step of this analysis is testing for stationarity of the variables. However the low power of traditional unit root tests is examined and proved in many studies but not taken into account in TAR cointegration studies in literature. This study shows that traditional unit root tests are unfavorable for the variables which have TAR structures. Because of this shortcoming of traditional unit root tests, these results must be supported with TAR unit root tests.
Keywords: Wage; Productivity; Non linear; TAR unit root; TAR cointegration; PURCHASING-POWER-PARITY; THRESHOLD COINTEGRATION; NONLINEAR ADJUSTMENT; SOLOW CONDITION; REAL WAGES; UNEMPLOYMENT; INFLATION; TESTS; MODEL; Social Sciences - Other Topics; Mathematics